Continuous support for women during childbirth - Hodnett, Ellen D (2012)
BACKGROUND: Historically, women have been attended and supported by other women during labour. However, in hospitals worldwide, continuous support during labour has become the exception rather than the routine. OBJECTIVES: Primary: to assess the effects of continuous, one-to-one intrapartum support compared with usual care. Secondary: to determine whether the effects of continuous support are influenced by: (1) routine practices and policies; (2) the provider’s relationship to the hospital and to the woman; and (3) timing of onset. SEARCH METHODS: We searched the Cochrane Pregnancy and Childbirth Group’s Trials Register (30 June 2012). SELECTION CRITERIA: All published and unpublished randomised controlled trials comparing continuous support during labour with usual care. DATA COLLECTION AND ANALYSIS: We used standard methods of The Cochrane Collaboration Pregnancy and Childbirth Group. Two review authors independently evaluated methodological quality and extracted the data. We sought additional information from the trial authors. We used random-effects analyses for comparisons in which high heterogeneity was present, and we reported results using the average risk ratio (RR) for categorical data and mean difference (MD) for continuous data. MAIN RESULTS: Twenty-two trials involving 15,288 women met inclusion criteria and provided usable outcome data. Results are of random-effects analyses, unless otherwise noted. Women allocated to continuous support were more likely to have a spontaneous vaginal birth (RR 1.08, 95% confidence interval (CI) 1.04 to 1.12) and less likely to have intrapartum analgesia (RR 0.90, 95% CI 0.84 to 0.96) or to report dissatisfaction (RR 0.69, 95% CI 0.59 to 0.79). In addition, their labours were shorter (MD −0.58 hours, 95% CI −0.85 to −0.31), they were less likely to have a caesarean (RR 0.78, 95% CI 0.67 to 0.91) or instrumental vaginal birth (fixed-effect, RR 0.90, 95% CI 0.85 to 0.96), regional analgesia (RR 0.93, 95% CI 0.88 to 0.99), or a baby with a low five-minute Apgar score (fixed-effect, RR 0.69, 95% CI 0.50 to 0.95). There was no apparent impact on other intrapartum interventions, maternal or neonatal complications, or breastfeeding. Subgroup analyses suggested that continuous support was most effective when the provider was neither part of the hospital staff nor the woman’s social network, and in settings in which epidural analgesia was not routinely available. No conclusions could be drawn about the timing of onset of continuous support. AUTHORS’ CONCLUSIONS: Continuous support during labour has clinically meaningful benefits for women and infants and no known harm. All women should have support throughout labour and birth.